Students’ Perceptions of EFL Teachers’ Teaching Styles in Post-Pandemic Classrooms: A Case Study - Aulia, Tegar; Eka Putri, Nabilah; Azizah, Rafida Nurul; Qomariyah, Wahyuni Lailatul (Universitas Ahmad Dahlan, 2025)
This study investigates students’ perceptions of English as a Foreign Language (EFL) teachers’ teaching styles in post-pandemic learning at SMA Negeri 4 Jayapura, Papua, Indonesia. The sudden transition from online to face-to-face learning following the COVID-19 pandemic has reshaped classroom dynamics, compelling teachers to adapt their instructional approaches. Using a mixed-methods design, data were collected through questionnaires and semi-structured interviews with senior high school students. The findings reveal that the majority of students preferred teachers who combined communicative and authoritative styles, balancing discipline with empathy and engagement. The study also found that the transition period highlighted students’ need for interactive and contextually relevant learning, as well as the importance of teacher adaptability in addressing diverse student motivations and learning preferences. These findings contribute to understanding how post-pandemic educational realities influence pedagogical effectiveness and classroom interaction in multilingual Indonesian settings.